Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine which of the given rational expressions equals 1 when [tex]\(x = -1\)[/tex], let's evaluate each expression step-by-step at [tex]\(x = -1\)[/tex].
1. For the expression [tex]\(\frac{3x - 2}{x^2 + 5}\)[/tex]:
[tex]\[ \frac{3(-1) - 2}{(-1)^2 + 5} = \frac{-3 - 2}{1 + 5} = \frac{-5}{6} \][/tex]
The value is [tex]\(\frac{-5}{6}\)[/tex]. This is not equal to 1.
2. For the expression [tex]\(\frac{-4x + 3}{x^2 - 8}\)[/tex]:
[tex]\[ \frac{-4(-1) + 3}{(-1)^2 - 8} = \frac{4 + 3}{1 - 8} = \frac{7}{-7} = -1 \][/tex]
The value is [tex]\(-1\)[/tex]. This is not equal to 1.
3. For the expression [tex]\(\frac{3x - 4}{6x^2}\)[/tex]:
[tex]\[ \frac{3(-1) - 4}{6(-1)^2} = \frac{-3 - 4}{6 \cdot 1} = \frac{-7}{6} \][/tex]
The value is [tex]\(\frac{-7}{6}\)[/tex]. This is not equal to 1.
4. For the expression [tex]\(\frac{2x^2}{x + 3}\)[/tex]:
[tex]\[ \frac{2(-1)^2}{-1 + 3} = \frac{2 \cdot 1}{2} = \frac{2}{2} = 1 \][/tex]
The value is [tex]\(1\)[/tex]. This is the expression we are looking for.
Therefore, the rational expression that equals 1 when [tex]\(x = -1\)[/tex] is [tex]\(\frac{2x^2}{x + 3}\)[/tex].
1. For the expression [tex]\(\frac{3x - 2}{x^2 + 5}\)[/tex]:
[tex]\[ \frac{3(-1) - 2}{(-1)^2 + 5} = \frac{-3 - 2}{1 + 5} = \frac{-5}{6} \][/tex]
The value is [tex]\(\frac{-5}{6}\)[/tex]. This is not equal to 1.
2. For the expression [tex]\(\frac{-4x + 3}{x^2 - 8}\)[/tex]:
[tex]\[ \frac{-4(-1) + 3}{(-1)^2 - 8} = \frac{4 + 3}{1 - 8} = \frac{7}{-7} = -1 \][/tex]
The value is [tex]\(-1\)[/tex]. This is not equal to 1.
3. For the expression [tex]\(\frac{3x - 4}{6x^2}\)[/tex]:
[tex]\[ \frac{3(-1) - 4}{6(-1)^2} = \frac{-3 - 4}{6 \cdot 1} = \frac{-7}{6} \][/tex]
The value is [tex]\(\frac{-7}{6}\)[/tex]. This is not equal to 1.
4. For the expression [tex]\(\frac{2x^2}{x + 3}\)[/tex]:
[tex]\[ \frac{2(-1)^2}{-1 + 3} = \frac{2 \cdot 1}{2} = \frac{2}{2} = 1 \][/tex]
The value is [tex]\(1\)[/tex]. This is the expression we are looking for.
Therefore, the rational expression that equals 1 when [tex]\(x = -1\)[/tex] is [tex]\(\frac{2x^2}{x + 3}\)[/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.